Economic Innovation: The Digitalization of Public Financial Management in The Administration of Regional Original Earnings in North Sulawesi - Junior Lakat; Tri Oldy Rotinsulu; Maryam Mangantar (Universitas Airlangga, 2026)
The exploration aims to analyze the capacity and application of public financial management digitalization across the electronification of local government transactions in improving the governance of Local Own-Source Earnings. This fact-finding engages a descriptive-analytical detail based on secondary data acquired from official government documents, regulatory shells, and institutional reports linked to regional financial digitalization policies. The discoveries indicate that public financial digitalization in Sulawesi Utara Province has been actively and coordinately enacted through the Regional Digitalization Acceleration and Expansion Team and has presented a path to strengthening LOSR governance, particularly in terms of transparency and accountability. This fact-finding concludes that the digitalization of public financial management is a major regional economic innovation. So far, to optimize its collision, it is advocated that local governments buttress the way absorption across earnings collection platforms, enhance digital position and technical training for financial management personnel, and expand quantifiable staging indicators to assess the quantitative collision of digitalization on regional proceeds. In addition, strengthening public trust and refining taxpayer digital literacy are essential to warrant extensive acceptance of non-cash agreements and uphold the viability of digital-based regional financial governa maintain sustainable customer loyalty in the Islamic fashion retail industry.